Protection on Nozel Maintenance, Isuzu Panther Machine Early Generation - I Wayan Suma Wibawa; I Gusti Bagus Wijaya Kusuma (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
Even though it is old, the existence and existence of Isuzu Panther cars in the 90s are still widely used, this is because in addition to the well-known / tested engine stubborn but also fuel efficient. To maintain the condition of the engine to stay fit, vehicle owners must pay attention to the maintenance of their cars regularly. One engine component that is vital and must receive special care is the Nozzle. The treatment of the nozzle is physical condition checking, cleaning and proper testing. This test is done by giving pressurized fuel to the nozzle, then we observe and analyze how the character of the spray. Testing pressure variations of 90 bar, 100 bar, 110 bar, 120 bar, and 130 bar (range of nozzle working pressure from the factory) using diesel, The characteristics of the fuel spray tested are the length of the spray penetration tip (L), speed spray (v or Uin), spray angle (Ɵ), and large distribution of granules formed at each pressure variation. From the test it is known, at 110 bar testing pressure has the best characteristics, both in terms of spray and the number of grains.